The Effect of Good Corporate Governance Mechanism on Company Financial Performance with Company Size As a Moderating Variable - Gogalim, Tya Thirani Lea; Pujiati, Diyah; Samekto, Agus (JEMBA: Journal of Economics, Management, Business and Accounting, 2024)
This research aims to examine the influence of good corporate governance mechanism consisting of independent commissioners, institutional ownership, and audit committees on company financial performance which is moderated by company size. This research used 86 companies with a population of manufacturing industry companies in the property and real estate sectors listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period, with a total sample of 344 financial report data. The data analysis technique used is the multiple linear regression analysis method. The research results show that independent commissioners and audit committees have no effect on financial performance and cannot be moderated by company size. On the other hand, institutional ownership influences the company's financial performance and can be moderated by company size